Efficacy of different acupuncture therapies on hand dysfunction in post-stroke patients: a systematic review and meta-analysis - Liu, Yuxiang; Zhou, Jing; Zheng, Jiawen; Chen, Jing (Frontiers in Neurology, 2025)
ObjectiveHand dysfunction is one of the main causes of disability in stroke. This systematic review and meta-analysis aimed to evaluate the efficacy of different types of acupuncture therapy in improving hand dysfunction among post-stroke patients.MethodsA comprehensive search was conducted across eight databases (PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure [CNKI], Chongqing VIP Chinese Scientific Journals Database [VIP], China Biology Medicine [CBM], and Wan Fang) to identify randomized controlled trials (RCTs). Forty-two RCTs involving 2,766 participants were included. Primary outcomes were the Brunnstrom Recovery Stage (BRS), Fugl-Meyer Assessment (FMA), and Lindmark scores; secondary outcomes included the Modified Ashworth Scale (MAS), Range of Motion (ROM), Manual Muscle Testing (MMT), and Modified Barthel Index (MBI).ResultsMeta-analyses demonstrated significant improvements in hand function across multiple outcomes: BRS (mean difference [MD] = 0.56, 95% confidence interval [CI]: 0.43–0.69), FMA (MD = 1.24, 95% CI: 0.96–1.53), MAS (MD = −0.48, 95% CI: −0.59 to −0.38), ROM (MD = 0.95, 95% CI: 0.64–1.26), and MBI (MD = 6.70, 95% CI: 4.85–8.55). Subgroup analyses revealed that electroacupuncture (EA) outperformed traditional acupuncture (TA) in improving BRS (p = 0.008). Heterogeneity was partially attributed to acupuncture modalities, with EA exhibiting lower variability compared to traditional methods.ConclusionThis meta-analysis supports the use of acupuncture, particularly EA, for enhancing hand function in post-stroke patients. EA demonstrates superior efficacy and consistency, suggesting its prioritization in clinical practice.